Association between Toxoplasma gondii Exposure and Suicidal Behavior in Patients Attending Primary Health Care Clinics - Alvarado-Esquivel, Cosme (Pathogens, 2021)
This study aimed to determine the association between suicidal behavior and T. gondii seroreactivity in 2045 patients attending primary care clinics. IgG antibodies against T. gondii were found in 37 (12.1%) out of 306 individuals with a history of suicidal ideation and in 134 (7.7%) of 1739 individuals without this history (OR: 1.64; 95% CI: 1.11–2.42; p = 0.01). Seropositivity to T. gondii was associated with suicidal ideation in women (OR: 1.56; 95% CI: 1.01–2.42; p = 0.03) and individuals aged ≤30 years (OR: 3.25; 95% CI: 1.53–6.88; p = 0.001). No association between the rates of high (>150 IU/mL) levels of anti-T. gondii IgG antibodies and suicidal ideation or suicide attempts was found. IgG antibodies against T. gondii were found in 22 of 185 (11.9%) individuals with a history of suicide attempts and in 149 (8.0%) of 1860 individuals without this history (OR: 1.54; 95% CI: 0.96–2.49; p = 0.06). The seroprevalence of T. gondii infection was associated with suicide attempts in individuals aged 31–50 years (OR: 2.01; 95% CI: 1.09–3.71; p = 0.02), and with more than three suicide attempts (OR: 4.02; 95% CI: 1.34–12.03; p = 0.008). Our results indicate that T. gondii exposure is associated with suicidal behavior among patients attending primary care clinics.